Believe me, Goldilocks rocks! : the story of the three bears as told by Baby Bear - Loewen, Nancy, 1964-; Avakyan, Tatevik, 1983- (Mankato, MN : Capstone, 2012)
Baby Bear, who wants to be called Sam, tells the true story of what happened when he and his parents went for a walk while their porridge cooled.
Picture Window Books.
Includes bibliographical references.
P-3.
4-8.
2.3.
Accelerated Reader AR
Keywords: Fairy tales; Humorous stories; Fairy tales; Humorous stories; Fairy tales; Humorous fiction